The Influence of Service Quality Affects Public Satisfaction Towards Police Image in Driving License Issuance at Boalemo District Police Traffic Unit - Karundeng, Deby R.; Suyanto, Mohamad Afan; Usu, Idrus; Mile, Kisran (LPPPIPublishing, 2024)
This study aims to investigate and analyze the impact of service quality on public satisfaction with the police image in the issuance of driver's licenses (SIM) at the Traffic Police Unit of Boalemo District Police. Through path analysis involving 100 respondents regarding SIM services at the Boalemo District Police, the findings indicate that service quality significantly influences the police image. Service quality also significantly affects public satisfaction, while the police image also significantly influences public satisfaction. Additionally, service quality indirectly influences public satisfaction through the mediating variable of the police image.